Evaluating aid impact - Howard White (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
The ultimate measure of aid effectiveness is how aid affects the lives of poor people in developing countries. The huge literature on aid's macroeconomic impact has remarkably little to say on this topic, and less still in terms of practical advice to government officials and aid administrators on how to improve development effectiveness. But there is an expanding toolbox of approaches to impact evaluation at the field level which can answer both questions of whether aid works, and, properly applied, why it works (or not, as the case may be). This paper lays out these approaches, describing some of their uses by official development agencies. I advocate a theory-based approach to impact evaluation design, as this is most likely to yield policy insights. Academics need to engage in these real world issues and debates if their work is to help alleviate the plight of the world's poor.
Keywords: O1; O12; O2; O22; 330; aid effectiveness; impact evaluation; quasi-experimental design; results agenda; Entwicklungshilfe; Makroökonomischer Einfluss; Entwicklung